ChatGPT in Brazilian K-12 science education - Monteiro, Fábio Ferreira; Souza, Paulo Victor Santos; da Silva, Marcelo Castanheira; Maia, José Robson; da Silva, Wagner Ferreira; Girardi, Daniel (Frontiers in Education, 2024)
This study investigates the perceptions of K-12 science teachers regarding the implications of ChatGPT on school assessments and the quality of students' education. A questionnaire was administered to K-12 science teachers from public and private schools across the five regions of Brazil: North, Northeast, South, Southeast, and Midwest. More than 400 teachers responded to the questionnaire. The conclusions regarding the opinions of the teachers who responded to the questionnaire were based on the Likert-type scale. The investigation covered various aspects, including the types and frequency of assessment methods used with their students. Additionally, the research delved into their opinions on whether ChatGPT would impact the quality of education and assessment methods, as well as their views on whether ChatGPT use should be deemed plagiarism or a similar infraction. The potential benefits of its use, as well as the challenges arising from it, are discussed in the context of the evolution of teaching and learning. As one of the results, it was found that among K-12 science teachers, there remains some skepticism regarding whether ChatGPT will enhance the quality of students' education and whether its use constitutes plagiarism or a similar infraction.